TRUST VALUE OF A DIVIDEND : AN EVIDENCE FROM INDONESIA - Ilat, Ventje; Budiarso, Novi Swandari; Wokas, Heince Rudy Nicky (Universitas Sam Ratulangi, 2019)
Even though there are many issues surrounding dividend policy, dividend remains one of the main goals for investors to achieve. The aim of this study is to find out determinants of dividend policy in Indonesia. Most of the samples in observed period have varieties of dividend policies. Data for this study was collected from 258 business entities in theÂ period between 2009 and 2012. For hypotheses testing, a binary logistic regression and factor analysis were used. The result from binary logistic regression showed that share price, earnings per share and current ratio are significant factors for dividend policy, while debt to equity ratio and corporate tax are insignificant. The insignificance of debt and tax was probably due to current ratio affected by accounting adjustments. Even though debt and tax are insignificant, they could not be ignored. Using factor analysis, it is confirmed that, most companies in this study have a similar objective through dividend policy, which is to maximize their share value in the stock market by considering profitability and liquidity on cash availability and also debt and tax. Dividends as a form of â€œtrust valueâ€ offered by companies to their shareholders stimulate the trust of investors or shareholders and resulting the increase of share price.